Armadillo meat intake was not associated with leprosy in a case control study, Curitiba (Brazil) - Schmitt, Juliano Vilaverde [UNESP]; Dechandt, Ivone Tod; Dopke, Gisele; Ribas, Maria Luiza; Cerci, Felipe Bochnia; Viesi, Juliana Maria Zucco; Marchioro, Helena Zenedin; Zunino, Mariana Martins Bardou; Miot, Hélio Amante [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2010)
Leprosy's progression and its maintained endemic status, despite the availability of effective treatments, are not fully understood and recent studies have highlighted the possibility of involved Mycobacterium leprae ambient reservoirs. Wild armadillos can carry leprosy and, because their meat is eaten by humans, development of the disease among armadillo meat consumers has been investigated. This study evaluated the frequency of armadillo meat intake among leprosy patients as well as age and gender matched controls with other skin diseases from a dermatological unit. Armadillo meat consumption among both groups was adjusted by demographic and socioeconomic covariates based on a conditional multiple logistic regression model. One hundred twenty-one cases and 242 controls were evaluated; they differed in socioeconomic variables such as family income, hometown population and access to treated water. The multivariate analysis did not show an association between the intake of armadillo meat and leprosy (odds ratio = 1.07; CI 95% 0.56-2.04), even when only cases with no known contacts were analyzed. We conclude that leprosy is not associated with the intake of armadillo meat in these patients.
Keywords: leprosy; Hansen's disease; HD; risk; case and control study; armadillos